PENGARUH KEMAMPUAN KERJA, LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN (STUDI PADA KARYAWAN TOKO EMAS SAMBAS PURWOREJO) - Syahbal, Habibi Fadhil; Widjajani, Susi; Utomo, Agus Saur (Journal of Economic, Bussines and Accounting (COSTING), 2025)
In an increasingly competitive business environment, companies are required to improve the quality of human resources to achieve optimal performance. Employee performance is a crucial factor in determining the success of an organization or company. Several factors influence employee performance, including work ability, work environment, and work motivation. This study focuses on Toko Emas Sambas Purworejo as the object of research. The sample consisted of 120 respondents, and data were collected using a questionnaire method. The data analysis was conducted using Smart PLS version 3.0. Based on the research findings and discussion, it can be concluded that: work ability has a positive and significant effect on employee performance; the work environment has a positive and significant effect on employee performance; and work motivation has a positive and significant effect on employee performance.